1997
DOI: 10.1902/jop.1997.68.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline‐Induced Intraoral Pharmacogenic Pigmentation: Case Reports and Review of the Literature

Abstract: Minocycline, a semi-synthetic tetracycline antibiotic, is well documented as being associated with pharmacogenic pigmentation of various tissues in humans and other mammals. The most obvious of these are skin pigmentation, but intraorally include "green" roots of erupted teeth, "black" roots of extracted teeth, a dark stain of the crowns of fully developed teeth, and "black" alveolar bone. This article presents five cases of "black" alveolar bone with photographic documentation of its progress. It also reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…Minocycline is a synthetic tetracycline used in the long term treatment of refractory acne vulgaris. It can cause pigmentation of the alveolar bone, which can be seen through the thin overlying oral mucosa (especially the maxillary anterior alveolar mucosa) as a gray discolouration [26]. Minocycline has also been reported to cause pigmentation of the tongue mucosa.…”
Section: Drug-induced Pigmentationmentioning
confidence: 99%
“…Minocycline is a synthetic tetracycline used in the long term treatment of refractory acne vulgaris. It can cause pigmentation of the alveolar bone, which can be seen through the thin overlying oral mucosa (especially the maxillary anterior alveolar mucosa) as a gray discolouration [26]. Minocycline has also been reported to cause pigmentation of the tongue mucosa.…”
Section: Drug-induced Pigmentationmentioning
confidence: 99%
“…Detailed discussion of this is beyond the scope of our report, but theories include the ability for minocycline to form an insoluble polymer with iron, and the contention that because minocycline binds to plasma proteins and is well distributed in collagen rich tissues (such as bone), subsequent oxidisation produces a pigmented biproduct 1–4. Minocycline pigmentation of teeth, unlike that caused by tetracyclines, does not clinically fluoresce in UV light but can fluoresce if treated in an acid medium 1–3 5…”
Section: Discussionmentioning
confidence: 99%
“…Although intraoral alveolar bone pigmentation by minocycline is well documented,5 it is reported infrequently in the orthopaedic literature. Whereas dental pigmentation becomes obvious to the patient and can be easily inspected, the discovery of pigmented skeletal bones is incidental during surgical exposure/autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[710] Westbury and Najera reported the incidence of minocycline staining of alveolar bone to be about 2% of the population taking the drug for two months or longer. [9] A literature search has also shown that the onset of discoloration can occur anytime from one month to many years after the initiation of treatment. [1011] In this patient, minocycline staining of the palatal torus occurred approximately three-and-a-half years after minocycline therapy was instituted.…”
Section: Discussionmentioning
confidence: 99%